Trends in age- and sex-specific lung cancer mortality in Europe and Northern America: analysis of vital registration data from the WHO Mortality Database between 2000 and 2017 - Baum, Philip; Winter, Hauke; Eichhorn, Martin E.; Rösch, Romina M.; Taber, Samantha; Christopoulos, Petros; Wiegering, Armin; Lenzi, Jacopo (European journal of cancer, 2022)
Background - In the context of new targeted therapies and immunotherapy as well as screening modalities for lung cancer patients, detailed mortality trends in Europe and Northern America are unknown. - Methods - Time-trend analysis using vital registration data of Northern America and Europe from the WHO Mortality Database (years 2000/2017). To assess improvements in lung cancer mortality, we performed a population-averaged Poisson autoregressive analysis. The average annual percent change (AAPC) was used as a summary measure of overall and country-specific trends in mortality. Second, we studied time trends of lung cancer incidence and smoking prevalence rates. - Findings - In the total population of 872·5 million people between 2015 and 2017, the average annual age-standardised mortality from lung cancer was 54·6 deaths per 100 000, with substantial differences across countries. Lung cancer was reported as the primary cause of death in 5·4 cases per 100 deaths. The age-standardised mortality rate decreased constantly (AAPC -1·5%) between 2000 and 2017. While mortality in men dropped annually by an average of −2·3%, mortality in women decreased by an average of −0·3%. This slight decline was driven exclusively by the USA. In contrast, 21 out of 31 countries registered a significant increase in female lung cancer mortality between 2000 and 2017, with Spain (AAPC 4·1%) and France (AAPC 3·6%) leading the list. - Interpretation - Despite overall decreases in lung cancer mortality trends, female mortality remained unchanged or increased significantly in all countries except the USA. National mortality outcomes reflect variabilities in tobacco control, screening, therapeutic advances, and access to health care.